Nilai Pendidikan Karakter Pada Tokoh Sri Rāma Dan Hanūmān Dalam Teks Rāmāyaṇa - Ni Putu Ratni; I Ketut Donder; I Ketut Sudarsana (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2019)
The research conducted base on the factual condition, which is delivered some phenomenons of character education implementation failure in order to form the students to be intellect and at the same time also keeping alive their nation spirit and soul; the purposes of the research were interpreting the answers of the research questions, which were consists of: (1) the character description of Sri Rāma and Hanūmān in the text of Rāmāyaṇa; (2) the description of character education values of Sri Rāma and Hanūmān in the text of Rāmāyaṇa; dan (3) the relevance between description of character education values of Sri Rāma and Hanūmān in the text of Rāmāyaṇa with the globalization era; some of the benefits of the research are delivering the results of study which can be used as a reference for the relevant further researches; and delivering importants points, which can be implemented in the world of formal, non-formal, and informal education system, so that the system will be able to strengthen the nation spirit and soul. The research conducted as qualitative research, utilized qualitative descriptive method; text analysis approach; descriptive data collection method; data collection technic of text analysis and documentation; descriptive data analysis; and qualitative descriptive of data presentation. The results of the research had delivered some descriptions as follows: (1) the character of Sri Rāma and Hanūmān in the text of Rāmāyaṇa are presenting the great and noble characteristic figures, which are very proper to be followed by everyone; (2) the character education values, which are arising from the characteristic of Sri Rāma and Hanūmān in the text of Rāmāyaṇa, consist of 18 national character education values. Therefore, their character education values are very proper to be utilized as a media in order to deliver the material of character education subject in Indonesia; and (3) the character education values of Sri Rāma and Hanūmān in the text of Rāmāyaṇa is very relevant with the globalization era, because they have potential ability to fulfill every criterion points of character education, either in national range, or in international one. Finally, it can be concluded that the character education from Sri Rāma and Hanūmān consist of big potential to be utilized as the guidance in order to deliver character education material that will be able to form the students to be smart, intellect, competitive, yet still respect on the nation spirit and soul of Indonesia.